PARENTAL BURNOUT PADA ORANG TUA GENERASI Z DAN IMPLIKASINYA TERHADAP RELASI ORANG TUA–ANAK: NARRATIVE LITERATURE REVIEW - Azahra Hardi Cusinia; Annisaislami Khairati; Mharchelya Mharchelya (Jurnal Keluarga Sehat Sejahtera, 2026)
Parental burnout has emerged as a critical issue among Generation Z parents in the context of increasing caregiving demands, economic pressures, and modern parenting expectations. This study aims to synthesize empirical and conceptual evidence on the impact of parental burnout on parent and child relationships among Generation Z parents. A Narrative Literature Review (NLR) was conducted by examining peer-reviewed journal articles indexed in Scopus published between 2021 and 2026. The literature was thematically analyzed to identify major patterns, psychological mechanisms, protective factors, and demographic and cultural contexts shaping the experience of burnout. The synthesis indicates that parental burnout is significantly associated with increased parent and child conflict, reduced emotional intimacy, and diminished family cohesion, with a bidirectional and self-reinforcing relationship between caregiving exhaustion and relational difficulties. The effects of burnout are mediated by emotional exhaustion, harsh parenting, low parental empathy, and impaired emotion regulation, whereas adaptive emotion regulation, coparenting quality, social support, and family resilience function as protective factors. Gender differences moderate both the experience and consequences of burnout, with mothers experiencing greater emotional impacts and paternal burnout being more closely linked to children’s psychological well-being. Personality traits, socioeconomic conditions, individualistic cultural orientations, and urban living further contribute to variations in burnout among Generation Z parents. Overall, parental burnout among Generation Z parents represents a dynamic and transactional process shaped by the interaction of emotional, behavioral, personality, and contextual factors, underscoring the need for multidimensional and gender-sensitive interventions to break the burnout–conflict cycle and safeguard children’s emotional well-being.